2012
DOI: 10.1063/1.4770227
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption of methanethiol clusters (CH3SH)n, n = 2–5, recorded with a time-of-flight mass spectrometer using IR depletion and VUV ionization

Abstract: We investigated IR spectra in the CH- and SH-stretching regions of size-selected methanethiol clusters, (CH(3)SH)(n) with n = 2-5, in a pulsed supersonic jet using infrared (IR)-vacuum ultraviolet (VUV) ionization. VUV emission at 132.50 nm served as the source of ionization in a time-of-flight mass spectrometer. Clusters were dissociated with light from a tunable IR laser before ionization. The variations in intensity of methanethiol cluster ions (CH(3)SH)(n)(+) were monitored as the IR laser light was tuned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The H s SCH P torsion mode was examined following the analysis by Cabaleiro-Lago et al , and observed a red shift of 15 ± 5 cm −1 for the dimer and the blue shift of 130 ± 6 cm −1 for trimer were observed as depicted in Table ST6. † The calculated vibrational frequencies for monomer, dimer, and trimers of methanethiol molecule corroborates exceedingly well with experimental results 9 compared to the frequencies computed by Cabaleiro-Lago et al favoring the existence of only three minima for dimer and trimer as against the previously reported five minima.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The H s SCH P torsion mode was examined following the analysis by Cabaleiro-Lago et al , and observed a red shift of 15 ± 5 cm −1 for the dimer and the blue shift of 130 ± 6 cm −1 for trimer were observed as depicted in Table ST6. † The calculated vibrational frequencies for monomer, dimer, and trimers of methanethiol molecule corroborates exceedingly well with experimental results 9 compared to the frequencies computed by Cabaleiro-Lago et al favoring the existence of only three minima for dimer and trimer as against the previously reported five minima.…”
Section: Resultssupporting
confidence: 89%
“…Subsequently, Lung Fu et al carried out time of flight mass spectrometry coupled with IR depletion and vacuum UV ionization studies on methanethiol clusters. 9 Their experiment revealed only the existence of a single most stable conformation of dimer without giving any information on the structural aspect. In the absence of rotationally resolved studies in their experiment, Lung Fu et al relied completely on Cabaleiro-Lago et al 's prediction at the MP2 level of theory for the conformation of the methanethiol dimer.…”
Section: Introductionmentioning
confidence: 99%
“…According to this comparison, the intense bands at 2941 and 3007 cm −1 and the weak band near 2609 cm −1 (red traces) are associated with the CH 3 SH moiety, whereas the medium band at 2912 cm −1 and perhaps two weaker ones near 2965 and 2983 cm −1 (blue traces) are associated with the CH 3 S moiety. The SH-stretching band at 2609 cm −1 , which is weak and blue-shifted by only 5 cm −1 from that of CH 3 SH, 31,32 indicates that the SH bond is not hydrogen-bonded and the interaction between CH 3 S and CH 3 SH is small.…”
mentioning
confidence: 98%
“…Actually, jet-cooled clusters have been well recognized to be ideal systems for investigating the intermolecular proton transfer as the cluster structures, and rovibronic states are certain before and after the reactions without the interference of the solvent environment. On the other hand, photoionization studies are often used to study thermodynamic and bonding information on hydrogen bonded clusters. For example, under vacuum ultraviolet (VUV) radiation, photoionization and photoinduced dissociation of an ethanol dimer were studied, where carbonium ions were observed and followed a Wagner–Meerwein rearrangement after surmounting the barriers of intra- and intermolecular methyl migrations. Also, dimethyluracil was found to readily dissociate in VUV radiation and produce a protonated monomer, where the proton transfer occurred from the methyl groups instead of the aromatic C–H groups .…”
Section: Introductionmentioning
confidence: 99%